PUBLIC RELATIONS STRATEGY IN ATTRACTING CUSTOMERS AT THE HOTEL FOUR SEASONS RESORT BALI AT JIMBARAN BAY - I Ketut Dika; Ni Nyoman Triyuni; I Nyoman Meirejeki (Journal of Applied Sciences in Travel and Hospitality, 2018)
This research was conducted at Hotel Four Seasons Resort Bali at Jimbaran Bay that aims to formulate a strategy of Public Relations in an attempt to attract customers. The purpose of this study are: (1) to know the strengths, weakness, opportunities and threats that affect Public Relations Public Relations strategy in attracting customers. (2) to find out the Public Relations strategy in attracting customers at the Hotel Four Seasons Resort Bali at Jimbaran Bay. This research is a descriptive qualitative research, which collects primary data through interviews and questionnaires. The method of determination of the sample was purposive sampling. Determination of internal and external factors with the use of EFAS and IFAS matrix to find out the position of the hotel and the SWOT analysis is used to decide the alternative Strategies. Based on the methods used, the position of the hotel is in cell V and the Strategies that can be used is forward integration. It can be implemented, namely the increased promotion by accentuating the uniqueness of the resort with a traditional Balinese village concept, through various distribution channels such as websites, social networks, magazines and TV (SO). Maintain the uniqueness of the resort in the form of traditional Balinese architecture with a modern touch (ST). Renew and add-on set reminders to review systems that haven't been ignored for all reviews that have been replied to (WO). Create an innovative event to inform the security conditions in the region of resort excellence and promoting at the same time maintained the uniqueness of the products of Four Seasons Resort Jimbaran (WT).